2013
DOI: 10.1007/s00705-013-1949-3
|View full text |Cite
|
Sign up to set email alerts
|

Equine herpesvirus type 1 (EHV-1)-induced rearrangements of actin filaments in productively infected primary murine neurons

Abstract: Equine herpesvirus type 1 (EHV-1) causes respiratory disease, abortion and neurological disorders in horses. In the present study, we investigated reorganization of the cytoskeleton in neurons infected with two EHV-1 strains: Jan-E (wild-type strain) and Rac-H (attenuated strain). The studies were performed on primary murine neurons, which are an excellent model for studying neurotropism and neurovirulence of EHV-1. We have demonstrated for the first time that EHV-1 infection causes rearrangements in the actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…Further analysis of the cytoskeleton rearrangement also indicated that each virus affects F-actin network in different way. The results are consistent with our previous studies (Turowska et al 2010, Słońska et al 2014. The Rac-H EHV-1 strain caused the destruction of the actin cytoskeleton in the infected neurons and ED cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Further analysis of the cytoskeleton rearrangement also indicated that each virus affects F-actin network in different way. The results are consistent with our previous studies (Turowska et al 2010, Słońska et al 2014. The Rac-H EHV-1 strain caused the destruction of the actin cytoskeleton in the infected neurons and ED cells.…”
Section: Discussionsupporting
confidence: 93%
“…The above-mentioned structures seemed to contribute to the direct spread of virus particles to adjacent cells without being exposed to the extracellular space. It seems that the neuropathogenic EHV-1 strain uses the same strategy to infect adjacent cells as the Jan-E EHV-1 (Słońska et al 2014). The literature data suggest that other herpesviruses also induce the formation of similar actin projections -HHV-1 in the Vero cells and BHK, VZV in the HFF cells or SuHV-1 in RK13 and PK15 cells (Favoreel et al 2005(Favoreel et al , 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we observed a non-uniform effect of tested EHV-1 strains on the cytoskeleton of the infected neurons. It seems very likely that both strains developed different strategies and mechanisms of interaction with the host cytoskeleton to facilitate efficient use of intracellular transport (Turowska et al, 2010;Słońska et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies we showed that during EHV-1 infection of primary murine neurons, both types of interactions between virus and actin cytoskeleton occurred. Jan-E EHV-1 (field strain) has caused formation of actin-containing projections that established intimate contact with adjacent cells and served to propel newly produced virions from cell to cell, whereas Rac-H EHV-1 (reference strain) induced the destruction of actin filaments, apparently to affect efficient egress (Słońska et al, 2014). As reported in literature, a number of viruses overcome a dense network of cortical actin presumably by myosin.…”
Section: Introductionmentioning
confidence: 83%
“…A detailed study of interactions between EHV-1 and host cells at the molecular level would be possible using a pure population of neurons. Such a model would also help avoid many confounding issues associated with studying latency and reactivation in vivo that can potentially obscure virus-cell interactions (8,9,20). In the present study, the main focus was on creating an appropriate in vitro model in which the complete suppression, as well as the restoration, of EHV-1 replication will be possible.…”
Section: Praca Oryginalnamentioning
confidence: 99%